Celecoxib mitigates genotoxicity induced by ionizing radiation in human blood lymphocytes - Seyed Jalal Hosseinimehr; Mahdieh Fathi; Arash Ghasemi; Seyedeh Nesa Rezaeian Shiadeh; Tayyeb Allahverdi Pourfallah (Wolters Kluwer Medknow Publications, 2017)
Ionizing radiation causes DNA damage and chromosome abbreviations on normal cells. The radioprotective effect of celecoxib (CLX) was investigated against genotoxicity induced by ionizing radiation in cultured human blood lymphocytes. Peripheral blood samples were collected from human volunteers and were incubated at different concentrations at 1, 5, 10 and 50 μM of CLX for two hours. At each dose point, the whole blood was exposed in vitro to 150 cGy of X-ray, and then the lymphocytes were cultured with mitogenic stimulation to determine the micronucleus frequency in cytokinesis blocked binucleated lymphocytes. Incubation of the whole blood with CLX exhibited a significant decrease in the incidence of micronuclei in lymphocytes induced by ionizing radiation, as compared with similarly irradiated lymphocytes without CLX treatment. The maximum reduction on the frequency of micronuclei was observed at 50 μM of CLX (65% decrease). This data may have an important possible application for the protection of human lymphocytes from the genetic damage induced by ionizing irradiation in human exposed to radiation.